Deviants Are Detected Faster at the End of Verse-Like Sound Sequences - Arrazola, Varun D. C. (Frontiers in Psychology, 2021)
Songs and poems from different traditions show a striking formal similarity: lines are flexible at the beginning and get more regular towards the end. This suggests that the free-beginning/strict-end pattern stems from a cognitive bias shared among humans. We propose that this is due to an increased sensitivity to deviants later in the line, resulting from a prediction-driven attention increase disrupted by line breaks. The study tests this hypothesis using an auditory oddball task where drum strokes are presented in sequences of eight, mimicking syllables in song or poem lines. We find that deviant strokes occurring later in the line are detected faster, mirrorring the lower occurrence of deviant syllables towards the end of verse lines.